Dextran-Sulfate Plasma Adsorption Lipoprotein Apheresis in Drug Resistant Primary Focal Segmental Glomerulosclerosis Patients: Results From a Prospective, Multicenter, Single-Arm Intervention Study - Raina, Rupesh; Krishnappa, Vinod; Sanchez-Kazi, Cheryl; Quiroga, Alejandro; Twombley, Katherine E.; Mathias, Robert; Lo, Megan; Chakraborty, Ronith; Mahesh, Shefali; Steinke, Julia; Bunchman, Timothy; Zaritsky, Joshua (Frontiers in Pediatrics, 2019)
Background: Focal segmental glomerulosclerosis (FSGS) causes end stage renal disease (ESRD) in significant proportion of patients worldwide. Primary FSGS carries poor prognosis and management of FSGS patients, refractory to standard treatments or resistant to steroids, remains a major challenge. Lipoprotein apheresis is a therapeutic approach for drug resistant primary FSGS and post-renal transplant primary FSGS recurrence. Objectives: To examine the safety and probable benefit at 1, 3, 6, 12 and 24-months following completion of apheresis treatment using Liposorber® LA-15 system in patients with nephrotic syndrome (NS), due to refractory primary FSGS or primary FSGS associated NS, in post renal transplant children. Material and methods: Prospective, multicenter, single-arm intervention study using Liposorber® LA-15 system. Patients ≤21 years old with drug resistant or drug intolerant NS secondary to primary FSGS with glomerular filtration rate (GFR) ≥60 ml/min/1.73m2 or post renal transplant patients ≤21 years old with primary FSGS associated NS were included in the study. Each patient had 12 dextran-sulfate plasma adsorption lipoprotein apheresis sessions over a period of 9 weeks. All patients were followed up at 1, 3, 6, 12 and 24-months following completion of treatment. Results: Of 17 patients enrolled, six were excluded from the outcome analysis (protocol deviations). Of the remaining 11 patients, all but one have completed apheresis treatments. Three patients were lost to follow-up immediately after completion of apheresis and excluded from outcome analysis. At one-month follow-up, 1 of 7 patients (14.3%) attained partial remission of NS while 2 of 4 subjects (50%) and 2 of 3 subjects (66.7%) had partial/complete remission at 3- and 6-months follow-up, respectively. One of two patients followed up for 12 months had complete remission and one patient had partial remission of NS after 24 months. Improved or stable eGFR was noted in all patients over the follow-up period. Conclusion: The results of our multicenter study showed improvement in the response rates to steroid or immunosuppressive therapy and induced complete or partial remission of proteinuria in some of the patients with drug resistant primary FSGS. The main limitation of our study is the small number of subjects and high dropout rate.